A method for preparing Au-Ag multi-stage nano-optical layer on surface of different rigid materials

By using Au-Ag alloy superplastic forming technology to prepare multi-level nano-optical layers on the surface of different rigid materials, the problems of long preparation cycle and complex process of optical layers are solved, and the process is simplified and the application is expanded, making it suitable for a variety of material surfaces.

CN122629475APending Publication Date: 2026-08-25MATERIAL INST OF CHINA ACADEMY OF ENG PHYSICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610735272.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing optical layers have long preparation cycles and complex processes, making it difficult to achieve efficient and simple optical layer preparation on the surfaces of various materials.

Method used

Au-Ag alloy superplastic forming technology is used to prepare Au-Ag multi-level nano-optical layers on the surface of porous anodized aluminum templates. The bonding of different rigid material surfaces is achieved by mechanical riveting, including steps such as mechanical or chemical processing, thermoplastic forming, pressure holding, cooling and corrosion.

Benefits of technology

It simplifies the process flow of optical layers, shortens the preparation cycle, expands the application scenarios of optical layers, is suitable for a variety of material surfaces, and has environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629475A_ABST
    Figure CN122629475A_ABST
Patent Text Reader

Abstract

The application provides a method for preparing Au-Ag multistage nano optical layer on the surface of various rigid materials. The method stacks porous anodic aluminum oxide / polishing template, polished Au-Ag alloy and mechanically / chemically treated rigid material in sequence, and after heating, pressurizing and pressure maintaining, the Au-Ag alloy is filled into the micro-holes of the template to form nanowire or mirror layer on one side, and is embedded into the microstructure on the surface of the rigid material to realize riveting on the other side; after cooling, the template is removed, and the Au-Ag primary nanowire array structure or mirror layer structure on the surface of the rigid material is prepared. The primary nanowire array structure on the surface of the material is subjected to etching treatment, secondary nanopores are constructed on the surface, multistage nano structure is formed, and the optical layer is obtained. The process flow of the application is simple, the experimental period is short, the electroplating process is not needed, the production process is green, environment-friendly and pollution-free, the controllability of the multistage nano structure is strong, and the Au-Ag multistage nano structure array, mirror layer and other optical layers can be formed on the surface of various rigid materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical layer materials technology, and specifically to a method for preparing Au-Ag multi-level nano-optical layers on the surface of different rigid materials. Background Technology

[0002] Optical layers, as core functional units of optoelectronic devices and detection systems, are widely used in photoelectric conversion, spectral modulation, sensing and recognition, and signal enhancement. In trace substance detection scenarios such as food safety, environmental safety, and biomedicine, optical layers are crucial for achieving highly sensitive and specific optical responses. Based on differences in functional mechanisms, optical layers mainly include two types: SERS substrates and mirrors.

[0003] Taking SERS substrate as an example, since the Raman signal is very weak, a signal enhancement mechanism is needed to achieve detection, and the SERS substrate is the core key to enhancing the Raman signal.

[0004] Taking mirrors as an example, they serve as core reflective elements in spectrometers, laser optical paths, and optical sensing systems, and are an important foundation for ensuring the signal-to-noise ratio and detection stability of optical systems.

[0005] Existing optical layers generally suffer from drawbacks such as poor signal spatial repeatability, long fabrication cycles, and complex processes. There is an urgent need to develop a universal method for in-situ fabrication of optical layers on various material surfaces. Therefore, developing a new method for fabricating optical layers that features a short fabrication cycle, simple process, and adaptability to various substrates is a pressing research challenge. Summary of the Invention

[0006] This invention aims to solve the problems of long preparation cycles and complex processes in optical layer fabrication, providing a multi-level nano-optical layer and its fabrication method. The Au-Ag alloy of this invention possesses excellent superplasticity and optical properties, and can be thermoplastically formed into micro / nano structures while simultaneously achieving bonding on different material surfaces through mechanical riveting. Utilizing the superplastic forming of Au-Ag alloy to prepare Au-Ag alloy micro / nano structures on porous anodic alumina templates (AAO) while simultaneously achieving bonding on different material surfaces can effectively shorten the process flow and expand application scenarios.

[0007] The technical method of the present invention is as follows: A method for preparing Au-Ag hierarchical nano-optical layers on the surface of different rigid materials includes the following steps: Step 1: Mechanically or chemically process the surface of the rigid material to roughen its surface and create micropores; Step 2: Select Au-Ag thin sheets and porous anodized aluminum templates of the same rigid material area. Polish one side of the Au-Ag alloy thin sheet. Stack the porous anodized aluminum template / polished silicon template, the polished Au-Ag alloy, and the rigid material processed in Step 1 in sequence. The polished surface of the Au-Ag alloy faces the porous anodized aluminum template / polished silicon template. Step 3: Heat the material treated in Step 2, apply pressure and hold the pressure for a period of time. The Au-Ag alloy undergoes superplastic forming. On the side facing the porous anodized aluminum template / polished silicon template, nanowires are filled into the micropores in the template to form nanowires. On the side facing the rigid material, nanowires are filled into the microstructure on the surface of the rigid material to achieve riveting. Step 4: Cool the material processed in Step 3, and then remove the porous anodized aluminum template / polished silicon template to obtain the Au-Ag primary nanowire array / mirror layer on the surface of the rigid material. Step 5: Etch the Au-Ag primary nanowire array on the surface of the rigid material to form secondary nanopores on the nanowire surface, thereby forming a secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material. The formation of the secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material and / or the Au-Ag mirror layer on the surface of the rigid material constitutes the multi-level nano-optical layer of the present invention.

[0008] Optionally, the rigid material includes one or more of metal, ceramic, glass, and semiconductor, and the melting point of the rigid material is not lower than the melting point of the Au-Ag alloy.

[0009] Optionally, in step 1, the mechanical or chemical processing includes one or more of the following: cutting, electrical discharge machining, laser drilling, and chemical etching.

[0010] Optionally, the heating time is 720~950K, the applied pressure is 4~7 kN, and the pressure holding time is 10~30 min.

[0011] Optionally, the porous anodized aluminum template / polished silicon template is removed by etching with a hot alkaline solution.

[0012] Optionally, the hot alkaline solution is a KOH solution and / or a NaOH solution, the concentration of the hot alkaline solution is 1~6 mol / L, and the temperature of the hot alkaline solution is 60~80℃.

[0013] Optionally, the corrosion is carried out by immersing the Au-Ag primary nanowire array on the surface of the rigid material in concentrated nitric acid, so that secondary nanopores are formed on the surface of the nanowires, and the immersion time is 2 to 30 minutes.

[0014] Optionally, the thickness of the Au-Ag alloy sheet is 0.1~10 mm, and the diameter of the Au-Ag sheet is 1~10 mm.

[0015] The present invention also provides an Au-Ag hierarchical nano-optical layer, which is prepared by the above method.

[0016] The beneficial effects of this invention are: 1. Compared with traditional optical layer preparation methods, the method of the present invention does not require complex processes such as electrodeposition and magnetron sputtering, and has the advantages of simple process, short preparation cycle and environmental friendliness.

[0017] 2. The method of the present invention has strong controllability, and the morphology and properties of Au-Ag hierarchical nanostructures can be controlled by using AAO templates of different sizes and etching times.

[0018] 3. This invention can form Au-Ag multi-level nanostructure arrays, mirror layers, and other optical layers on the surface of different types of rigid materials. Attached Figure Description

[0019] Figure 1 This is a flowchart illustrating the preparation process in Example 1 of the present invention; Figure 2 This is a flowchart illustrating the preparation process in Example 2 of the present invention; Figure 3 This is a flowchart illustrating the preparation process in Example 3 of the present invention. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] This invention provides a method for preparing Au-Ag hierarchical nano-optical layers on the surface of different rigid materials, comprising the following steps: Step 1: Mechanically or chemically process the surface of the rigid material to roughen it and create micropores.

[0022] In this embodiment, the rigid material includes one or more of metals, ceramics, glass, and semiconductors, and the melting point of the rigid material is not lower than that of the Au-Ag alloy. Further, the metal includes one or more of ferrous metals, non-ferrous metals, and refractory metals. The ferrous metal may be iron or steel, the non-ferrous metal may be titanium, and the refractory metal may be tungsten. The ceramic includes one or more of silicate ceramics, oxide ceramics, and nitride ceramics. The glass includes Euton glass and / or tempered glass. The semiconductor includes silicon wafers and / or germanium wafers.

[0023] In this embodiment, the optical layer includes two types: SERS substrate and mirror.

[0024] In this embodiment, mechanical or chemical processing includes one or more of the following: cutting, electrical discharge machining, laser drilling, and chemical etching.

[0025] In this embodiment, the diameter of the rigid material is 4~12 mm and the thickness is 0.5~10 mm.

[0026] In this embodiment, the diameter of the micropores is 0.5~1.5 mm, and the depth is 0.5~2 mm. Here, the micropores affect the diameter of the secondary nanopores on the surface after the reaction.

[0027] Step 2: Select Au-Ag thin sheets and porous anodized aluminum templates with the same area of ​​rigid material. Polish one side of the Au-Ag alloy thin sheet. Stack the porous anodized aluminum template / polished silicon template, the polished Au-Ag alloy, and the rigid material processed in Step 1 in sequence. The polished surface of the Au-Ag alloy faces the porous anodized aluminum template / polished silicon template.

[0028] In this embodiment, the thickness of the Au-Ag alloy sheet is 0.1~10 mm, and the diameter of the Au-Ag sheet is 1~10 mm.

[0029] In this embodiment, the dimensions of the porous anodized aluminum template / polished silicon template are consistent with those of the Au-Ag alloy sheet.

[0030] Step 3: Heat the material treated in Step 2, apply pressure and hold the pressure for a period of time. The Au-Ag alloy undergoes superplastic forming. On the side facing the porous anodized aluminum template / polished silicon template, nanowires are filled into the micropores in the template to form nanowires. On the side facing the rigid material, nanowires are filled into the microstructure on the surface of the rigid material to achieve riveting bonding.

[0031] In this embodiment, the heating time is 720~950K, the applied pressure is 4~7 kN, and the holding time is 10~30min. For example, the applied pressure can be 5 kN or 6 kN, and the holding time can be 15min or 20min.

[0032] Step 4: Cool the material processed in Step 3, and then remove the porous anodized aluminum template / polished silicon template to obtain the Au-Ag primary nanowire array / mirror layer on the surface of the rigid material.

[0033] In this embodiment, the porous anodic aluminum oxide template is removed by corrosion with a hot alkaline solution. The hot alkaline solution is an alkaline solution such as KOH or NaOH, with a concentration of 1~6 mol / L and a temperature of 60~80℃. For example, the temperature can be 70℃ or 75℃.

[0034] Step 5 involves etching the Au-Ag primary nanowire array on the surface of the rigid material to form secondary nanopores on the nanowire surface, thereby forming a secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material. The formation of the secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material and / or the Au-Ag mirror layer on the surface of the rigid material constitutes the multi-level nano-optical layer of this invention.

[0035] In this embodiment, corrosion is achieved by immersing the Au-Ag primary nanowire array on the surface of a rigid material in concentrated nitric acid, thereby forming secondary nanopores on the nanowire surface. The immersion time is 2–30 min. For example, the time can be 5 min, 15 min, or 25 min.

[0036] The present invention also provides an Au-Ag hierarchical nano-optical layer, which is prepared by the above method.

[0037] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0038] The present invention will be described in detail below through embodiments and experimental examples. However, these are merely examples and do not limit the present invention in any way.

[0039] Example 1 Au-Ag hierarchical nano-optical layers were fabricated on the surfaces of different rigid materials. The specific process flow is as follows: Figure 1 As shown, it includes the following steps: Step 1: Roughening the surface of rigid materials: Select a glass with a diameter of 6 mm and a thickness of 5 mm, and use electrical discharge machining to roughen the surface of the glass, creating micropores with a diameter of about 0.5 mm and a depth of about 1 mm.

[0040] Step 2: Preparation of Au-Ag hierarchical nano-optical layer materials on the surface of different rigid materials: A 6 mm diameter and 1 mm thick Au-Ag alloy sheet was selected. One side of the Au-Ag alloy sheet was polished. Then, the Au-Ag alloy sheet was placed between an AAO template (with dimensions matching the Au-Ag alloy sheet) and the treated glass material, with the polished side facing the AAO template and the other side facing the treated glass material from step 1. After stacking, all three were simultaneously heated to 773 K and subjected to a pressure of 5.7 kN for 10 min. During this process, the Au-Ag alloy underwent thermoplastic forming, filling the micropores into the glass material from the side facing it.

[0041] Step 3: Cool the Au-Ag alloy, AAO template, and rigid material to below 200℃ to prevent the Au-Ag alloy nanostructure from springing back. Remove the AAO template in a 3 mol / L KOH solution at 60℃ to obtain an Au-Ag alloy nanowire array on the glass material surface.

[0042] Step 4: Immerse the Au-Ag nanowire array on the surface of the rigid material in Step 3 into concentrated nitric acid solution for 2 minutes to form secondary nanopores on the nanowire surface.

[0043] Example 2 Au-Ag hierarchical nano-optical layers were fabricated on the surfaces of different rigid materials. The specific process flow is as follows: Figure 2 As shown, it includes the following steps: Step 1: Roughening the surface of rigid materials: A ceramic material with a diameter of 10 mm and a thickness of 3 mm was selected. The surface of the ceramic was processed by laser drilling to roughen it and create micro-pores with a diameter of about 1 mm and a depth of about 1.5 mm.

[0044] Step 2: Fabrication of Au-Ag hierarchical nano-optical layers on the surfaces of different rigid materials: A 10 mm diameter, 1.5 mm thick Au-Ag alloy sheet was selected. One side of the Au-Ag alloy sheet was polished. Then, the Au-Ag alloy sheet was placed between an AAO template (of the same size as the Au-Ag alloy sheet) and the treated ceramic material, with the polished side facing the AAO template and the other side facing the treated ceramic material from step 1. After stacking, all three were simultaneously heated to 896 K and subjected to a 7 kN pressure for 15 min. During this process, the Au-Ag alloy underwent thermoplastic forming, filling the micropores into the ceramic material from the side facing the alloy.

[0045] Step 3: Cool the Au-Ag alloy, AAO template, and ceramic material to below 200℃ to prevent the Au-Ag alloy nanostructure from springing back. Remove the AAO template in a 2 mol / L KOH solution at 70℃ to obtain an Au-Ag alloy nanowire array on the surface of the ceramic material.

[0046] Step 4: Immerse the Au-Ag nanowire array on the surface of the rigid material in Step 3 into concentrated nitric acid solution for 4 minutes to form secondary nanopores on the nanowire surface.

[0047] Example 3 Au-Ag hierarchical nano-optical layers were fabricated on the surfaces of different rigid materials. The specific process flow is as follows: Figure 3 As shown, it includes the following steps: Step 1: Roughening the surface of rigid materials: A titanium alloy material with a diameter of 5 mm and a thickness of 10 mm was selected. The surface of the titanium alloy was processed by wire cutting to roughen it and create micro-pores with a diameter of about 0.6 mm and a depth of about 2 mm.

[0048] Step 2: Preparation of Au-Ag hierarchical nano-optical layer materials on the surface of different rigid materials: A 5 mm diameter, 0.8 mm thick Au-Ag alloy sheet was selected. One side of the Au-Ag alloy sheet was polished. Then, the Au-Ag alloy sheet was placed between an AAO template (of the same size as the Au-Ag alloy sheet) and the treated titanium alloy material, with the polished side facing the AAO template and the other side facing the treated titanium alloy material from step 1. After stacking, all three were simultaneously heated to 723 K and subjected to a pressure of 4.3 kN for 30 min. During this process, the Au-Ag alloy underwent thermoplastic forming, filling the micropores with the side facing the titanium alloy material.

[0049] Step 3: Cool the Au-Ag alloy, AAO template, and titanium alloy material to below 200℃ to prevent the Au-Ag alloy nanostructure from springing back. Remove the AAO template in a 1 mol / L KOH solution at 80℃ to obtain an Au-Ag alloy nanowire array on the surface of the titanium alloy material.

[0050] Step 4: Immerse the Au-Ag nanowire array on the surface of the rigid material in Step 3 in concentrated nitric acid solution for 30 minutes to form secondary nanopores on the nanowire surface.

[0051] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.

[0052] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing Au-Ag hierarchical nano-optical layers on the surface of different rigid materials, characterized in that, Includes the following steps: Step 1: Mechanically or chemically process the surface of the rigid material to roughen its surface and create micropores; Step 2: Select Au-Ag thin sheets and porous anodized aluminum templates of the same rigid material area. Polish one side of the Au-Ag alloy thin sheet. Stack the porous anodized aluminum template / polished silicon template, the polished Au-Ag alloy, and the rigid material processed in Step 1 in sequence. The polished surface of the Au-Ag alloy faces the porous anodized aluminum template / polished silicon template. Step 3: Heat the material treated in Step 2, apply pressure and hold the pressure for a period of time. The Au-Ag alloy undergoes superplastic forming. On the side facing the porous anodized aluminum template / polished silicon template, nanowires are filled into the micropores in the template to form nanowires. On the side facing the rigid material, nanowires are filled into the microstructure on the surface of the rigid material to achieve riveting. Step 4: Cool the material processed in Step 3, and then remove the porous anodized aluminum template / polished silicon template to obtain the Au-Ag first-order nanowire array / mirror layer on the surface of the rigid material. Step 5: Etch the Au-Ag primary nanowire array on the surface of the rigid material to form secondary nanopores on the nanowire surface, thereby forming a secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material. The formation of the secondary nanoporous structure on the surface of the Au-Ag primary nanowires on the surface of the rigid material and / or the Au-Ag mirror layer on the surface of the rigid material constitutes the multi-level nano-optical layer of the present invention.

2. The method according to claim 1, characterized in that, The rigid material includes one or more of metals, ceramics, glass, and semiconductors, and the melting point of the rigid material is not lower than that of the Au-Ag alloy.

3. The method according to claim 1, characterized in that, In step 1, the mechanical or chemical processing includes one or more of the following: cutting, electrical discharge machining, laser drilling, and chemical etching.

4. The method according to claim 1, characterized in that, The heating time is 720~950K, the applied pressure is 4~7 kN, and the pressure holding time is 10~30 min.

5. The method according to claim 1, characterized in that, The porous anodized aluminum template / polished silicon template is removed by corrosion with a hot alkaline solution.

6. The method according to claim 5, characterized in that, The hot alkaline solution is a KOH solution and / or a NaOH solution, with a concentration of 1~6 mol / L and a temperature of 60~80℃.

7. The method according to claim 1, characterized in that, The corrosion is achieved by immersing the Au-Ag primary nanowire array on the surface of a rigid material in concentrated nitric acid, which forms secondary nanopores on the surface of the nanowires. The immersion time is 2 to 30 minutes.

8. The method according to claim 1, characterized in that, The Au-Ag alloy sheet has a thickness of 0.1~10 mm and a diameter of 1~10 mm.

9. An Au-Ag hierarchical nano-optical layer, characterized in that, It is prepared by the method described in any one of claims 1 to 8.